Exceptionally strong summer-like zonal wind reversal in the upper mesosphere during winter 2015/16 - G. Stober; V. Matthias; C. Jacobi; S. Wilhelm; J. Höffner; J. L. Chau (Annales Geophysicae, 2017)
The 2015/16 Northern Hemisphere winter season was marked by peculiarities in the circulation pattern in the high-latitude mesopause region. Wind measurements from the Andenes (69° N, 13° E) meteor radar show westward winds below 84 km and eastward winds above. This wind pattern in the zonal wind was observable between the end of December 2015 and the end of January 2016, i.e., conditions that are typical for the summer were found during winter. Additional meteor radar measurements at midlatitude stations did not show such a zonal wind reversal but indicate, together with the polar latitude stations, a reversal of the horizontal temperature gradient. This is confirmed by global satellite measurements. Therefore, it is plausible that the polar latitude summer-like zonal wind reversal in December–January is in accordance with the reversed horizontal temperature gradient assuming a thermal wind balance between mid- and polar latitudes. The reversed horizontal temperature gradient itself is induced by stationary planetary waves at lower and midlatitudes in the mesosphere, leading to a weakening of the residual circulation above the European sector.